2007
DOI: 10.1186/1472-6963-7-158
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trials for evaluating the prescribing impact of information meetings led by pharmacists and of new information formats, in General Practice in Italy

Abstract: BackgroundSuboptimal translation of valid and relevant information in clinical practice is a problem for all health systems. Lack of information independent from commercial influences, limited efforts to actively implement evidence-based information and its limited comprehensibility are important determinants of this gap and may influence an excessive variability in physicians' prescriptions. This is quite noticeable in Italy, where the philosophy and methods of Evidence-Based Medicine still enjoy limited diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Only a few studies have showed effective interventions to modify prescribing habits [18, 19], in particular for NSAIDs [20]. A few other studies have tried to evaluate the efficacy of removing economic barriers to appropriate drug prescribing, but not specifically regarding paracetamol [12, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have showed effective interventions to modify prescribing habits [18, 19], in particular for NSAIDs [20]. A few other studies have tried to evaluate the efficacy of removing economic barriers to appropriate drug prescribing, but not specifically regarding paracetamol [12, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the first group, some studies show that antibiotics were prescribed indiscriminately, inappropriately and injudiciously to manage the oral disease (29). When it comes to the pharmaceutical industry, some studies have shown that its influence over the representatives of pharmaceutical sales significantly contribute to the inadequate prescription of drugs (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, general practitioners from Friuli Venezia-Giulia (another region in Northern Italy), initially supposed to take part in the RCTs, did not in the end do so because their representatives and the Regional Health Authority disagreed. Moreover, one more RCT was originally planned in Sardinia (a large island in Southern Italy), to compare three different strategies of information delivery to solo general practitioners: [21] this trial did not take place for similar reasons as in Friuli Venezia-Giulia. Involvement of doctors’ organizations and strong endorsement of Health Authorities are crucial in implementing such an anti-promotional intervention; doctors may see these interventions as top-down, cost-saving approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Two consecutive cluster trials, stemming from the same study protocol, were carried out in spring 2007 and autumn-winter 2007–08, respectively, in five Provinces of the Emilia Romagna region (Bologna, Forlì, Modena, Parma and Reggio Emilia, totalling about 2,200,000 inhabitants) involving all practising NHS General Practitioners. [21] .…”
Section: Methodsmentioning
confidence: 99%